Influenza Vaccine Effectiveness in the 2011–2012 Season: Protection Against Each Circulating Virus and the Effect of Prior Vaccination on Estimates. (13th November 2013) - Ohmit, Suzanne E.; Thompson, Mark G.; Petrie, Joshua G.; Thaker, Swathi N.; Jackson, Michael L.; Belongia, Edward A.; Zimmerman, Richard K.; Gaglani, Manjusha; Lamerato, Lois; Spencer, Sarah M.; Jackson, Lisa; Meece, Jennifer K.; et al.
Abstract : Influenza vaccine effectiveness in preventing medically attended influenza in the 2011–2012 season was modest overall, with low effectiveness against the predominant A (H3N2) virus. This may be related to antigenic drift, but past history of vaccination might also play a role. Abstract: Background. Each year, the US Influenza Vaccine Effectiveness Network examines the effectiveness of influenza vaccines in preventing medically attended acute respiratory illnesses caused by influenza. Methods. Patients with acute respiratory illnesses of ≤7 days' duration were enrolled at ambulatory care facilities in 5 communities. Specimens were collected and tested for influenza by real-time reverse-transcriptase polymerase chain reaction. Receipt of influenza vaccine was defined based on documented evidence of vaccination in medical records or immunization registries. Vaccine effectiveness was estimated in adjusted logistic regression models by comparing the vaccination coverage in those who tested positive for influenza with those who tested negative. Results. The 2011–2012 season was mild and peaked late, with circulation of both type A viruses and both lineages of type B. Overall adjusted vaccine effectiveness was 47% (95% confidence interval [CI], 36–56) in preventing medically attended influenza; vaccine effectiveness was 65% (95% CI, 44–79) against type A (H1N1) pdm09 but only 39% (95% CI, 23–52) against type A (H3N2). Estimates of vaccine effectiveness against both type B lineages were similar (overall, 58%; 95% CI, 35–73). An apparent negative effect of prior year vaccination on current year effectiveness estimates was noted, particularly for A (H3N2) outcomes. Conclusions. Vaccine effectiveness in the 2011–2012 season was modest overall, with lower effectiveness against the predominant A (H3N2) virus. This may be related to antigenic drift, but past history of vaccination might also play a role.